2020
DOI: 10.26552/com.c.2020.4.182-190
|View full text |Cite
|
Sign up to set email alerts
|

Safety Assessment of Adjacent Roads Sections via Maximum Entropy Driver's Perception Field

Abstract: Characteristics have been developed, by which the boundaries of coherence of adjacent road sections are established in accordance with requirements for the traffic safety. The coordination of adjacent sections of the road is carried out taking into account the driver’s behavior program, which is presented in the work as a value of the maximum entropy of his perception field. The choice of this criterion is determined by the possibility of a comprehensive assessment of many road environment factors that influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Perhaps, only the works of Ukrainian authors [104,105] highlight the relationship between the entropy characteristics of the environment and road accident rates. The authors [104,105] presented the results of studying the impact of the driver's perception field entropy on road accident rates.…”
Section: Previous Studies On the Impact Of Traffic Flow Entropy On Ro...mentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps, only the works of Ukrainian authors [104,105] highlight the relationship between the entropy characteristics of the environment and road accident rates. The authors [104,105] presented the results of studying the impact of the driver's perception field entropy on road accident rates.…”
Section: Previous Studies On the Impact Of Traffic Flow Entropy On Ro...mentioning
confidence: 99%
“…Perhaps, only the works of Ukrainian authors [104,105] highlight the relationship between the entropy characteristics of the environment and road accident rates. The authors [104,105] presented the results of studying the impact of the driver's perception field entropy on road accident rates. N. Kulbashna et al have observed, drawing on findings from [88], that an increase in the differential of maximum entropy between neighboring areas correlates with a decline in the accident rate, albeit up to a specific threshold [104].…”
Section: Previous Studies On the Impact Of Traffic Flow Entropy On Ro...mentioning
confidence: 99%
See 1 more Smart Citation